2012
DOI: 10.1158/2159-8290.cd-12-0041
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide DNA Methylation Events in TMPRSS2–ERG Fusion-Negative Prostate Cancers Implicate an EZH2-Dependent Mechanism with miR-26a Hypermethylation

Abstract: Prostate cancer is the second most common cancer among men worldwide. Alterations in the DNA methylation pattern can be one of the leading causes for prostate cancer formation. This study is the fi rst high-throughput sequencing study investigating genome-wide DNA methylation patterns in a large cohort of 51 tumor and 53 benign prostate samples using methylated DNA immunoprecipitation sequencing. Comparative analyses identifi ed more than 147,000 cancer-associated epigenetic alterations. In addition, global me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
97
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(108 citation statements)
references
References 55 publications
9
97
0
2
Order By: Relevance
“…6C; χ 2 =13.66; P=0.008). Thus, in corroboration to previous reports (4,14), our data suggests a more pronounced role of epigenetic alterations in ETS-fusion negative cases. Although, 6 of the 50 SPINK1+ cases failed to show any expression of EZH2, pointing that an alternative mechanism may be involved in SPINK1 regulation or possibly miRNA-338/-421 genomic deletion could be a cause in such cases.…”
supporting
confidence: 92%
See 3 more Smart Citations
“…6C; χ 2 =13.66; P=0.008). Thus, in corroboration to previous reports (4,14), our data suggests a more pronounced role of epigenetic alterations in ETS-fusion negative cases. Although, 6 of the 50 SPINK1+ cases failed to show any expression of EZH2, pointing that an alternative mechanism may be involved in SPINK1 regulation or possibly miRNA-338/-421 genomic deletion could be a cause in such cases.…”
supporting
confidence: 92%
“…Recently, a new subtype of ETS-fusion-negative tumors has been defined by frequent mutations in the epigenetic regulators and chromatin remodelers (55). Yet another study, using genome-wide methylated DNAimmunoprecipitation sequencing revealed higher number of methylation events in TMPRSS2-ERG fusion-negative as compared to normal and TMPRSS2-ERG fusion-positive PCa specimens (14), thus collectively, these independent findings reaffirm the critical role of epigenetic pathways engaged in the pathogenesis of SPINK1+ subtype.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Using high-throughput genome sequencing and DNA methylation analyses, .147 000 cancer-associated epigenetic alterations were observed in 51 tumour and 53 benign prostate samples; the specific nature of these alterations were dependent on the presence of absence of a TMPRSS2-ERG rearrangement. 52 This observation of differential methylation events in fusion-negative tumours (based on enhancer of zeste homologue 2 (EZH2) gene activation) explains CaP carcinogenesis in the 50% of patients who are TMPRSS2-ERG fusion-negative. Systematic overviews of studies for the prognostic role of specific gene methylation (e.g.…”
Section: Genetic Instability and Genomic Assays In Localized Prostatementioning
confidence: 99%